Optimization of Residual Stresses in Laser-Mixed WC(Co,Ni) Coatings - Liu, C.W.; Jean, M.D.; Wang, Q.T.; Chen, B.S. (Проблемы прочности, 2019)
A ternary mixture of tungsten carbide (WC), cobalt (Co), and nickel (Ni) powders is prepared to form ceramic-metal composite coatings employed for laser cladding of 40Cr steel. This coating is investigated using the mixture design to evaluate the influence of its ratios on the residual stresses in the clads. The WC/Co/Ni ternary mixture exhibits higher residual stresses than those of the Co/Ni or WC/Ni binary mixtures, except for the WC/Co one. Single WC, Co, or Ni designs illustrate a high sensitivity of residual stresses, cracks pass through the interior of WC particles rather than around them, and the cracks mostly propagate along the eutectic phases at 50%Co–50%WC. A reduced special quartic model in the mixture design exhibits excellent fit, predicted and experimental values of residual stresses for these laser clads are in good agreement.